Integrating Materials Flow, Production Control and Quality Control: a Proposal and Case Study - Fernandes, Flavio Cesar Faria; Filho, Moacir Godinho; Bonney, Maurice (Brazilian Journal of Operations & Production Management, 2010)
This paper presents a proposal for integrating materials flow, production control and quality control. The proposal is based on three principles: that materials flow must be as simple as possible, that a production control system must be compatible with the production system and that the production pace must take account of demand, capacity and quality. The paper examines the dependent relationship between Production Control (PC) and Quality Control (QC) since this relationship provides opportunities for improving manufacturing performance. A case study performed at the world’s largest pencil factory suggests that the proposal contributes effectively to operations management at the shop floor level.